Reconstitution of an efficient thymidine salvage pathway in Saccharomyces cerevisiae - Vernis, Laurence (Oxford University Press, 2003)
The budding yeast Saccharomyces cerevisiae is unable to incorporate exogenous nucleosides into DNA. We have made a number of improvements to existing strategies to reconstitute an efficient thymidine salvage pathway in yeast. We have constructed strains that express both a nucleoside kinase as well as an equilibrative nucleoside transporter. By also deleting the gene encoding thymidylate synthase (CDC21) we have constructed strains that are entirely dependent upon exogenous thymidine for viability and that can grow with normal kinetics at low thymidine concentrations. Using this novel approach, we show that depletion of a single deoxyribonucleoside causes reversible arrest of cells in S phase with concomitant phosphorylation and activation of the S phase checkpoint kinase, Rad53. We show that this strain also efficiently incorporates the thymidine analogue, BrdU, into DNA and can be used for pulse–chase labelling.